Women’s human rights and internal migration in San Cristóbal de Las Casas: analysis of the testimony of a young indigenous Tzotzil woman. - Castillo Rojas, Mariana (2020)
Women who migrate internally in Mexico, especially those from indigenous municipalities, face situations of discrimination and violence, as a result of the cross marginalization they receive due to their gender, ethnicity and social class.  Additionally, the lack of information about their human rights and how to make them effective places them in a particularly vulnerable position.  In the present article, this reality is examined from the analysis of the testimony of a Tzotzil woman who migrated to San Cristóbal de Las Casas, Chiapas, when she was very young, for which a semi-structured interview was conducted.  The life experience shared by the interviewee evidenced that the structural violence suffered by indigenous communities, in terms of access to quality public services, leads to forced migration, which in turn exposes women to particular forms of discrimination and exclusion.  Among the main conclusions of this work is the relevance of mutual support networks to counter the lack of information about their human rights and jointly face the different types of violence to which they are subjected.